1996
DOI: 10.1002/(sici)1098-2744(199611)17:3<144::aid-mc6>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

A cytochrome P4502E1 genetic polymorphism and tobacco smoking in breast cancer

Abstract: Known breast-cancer risk factors account for only part of the variability in breast-cancer incidence. Tobacco smoke is not commonly considered a breast carcinogen, but many of its constituents, such as N-nitrosamines, are carcinogenic in laboratory animal studies. Herein, we assessed a cytochrome P4502E1 (CYP2E1) genetic polymorphism (a Dral restriction enzyme site in intron 6) as a risk factor for breast cancer in both premenopausal and postmenopausal women. Because N-nitrosamines are metabolically activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…In an early case-control study (272 cases and 334 controls, a subset of a larger study with information on genotype), Shields et al (44) showed smoking increased breast cancer risk among premenopausal but not postmenopausal women with 6CYP2E1 variant (a DraI restriction enzyme site in intron 6). Because CYP2E1 enzyme is involved in the metabolic activation of N-nitrosamines, which are contained in tobacco smoke, it is possible that the polymorphism will modify susceptibility to breast cancer due to smoking.…”
Section: Resultsmentioning
confidence: 99%
“…In an early case-control study (272 cases and 334 controls, a subset of a larger study with information on genotype), Shields et al (44) showed smoking increased breast cancer risk among premenopausal but not postmenopausal women with 6CYP2E1 variant (a DraI restriction enzyme site in intron 6). Because CYP2E1 enzyme is involved in the metabolic activation of N-nitrosamines, which are contained in tobacco smoke, it is possible that the polymorphism will modify susceptibility to breast cancer due to smoking.…”
Section: Resultsmentioning
confidence: 99%
“…A large volume of literature correlates CYP2E1 polymorphisms with a multitude of diseases, including ALD, diabetes, and several different cancers (31,33,35,36,38,42,43,80,81). A majority of the genetic screens so far have targeted either the 5Ј-promoter region, which regulates CYP2E1 transcription rates (CYP2E1*5B), or the catalytic domain (CYP2E1*6), which alters the catalytic rates of the enzyme (32).…”
Section: Discussionmentioning
confidence: 99%
“…Vodicka et al (33) showed that polymorphisms in the 5Ј-flanking region and in the DraI site in intron 6 are significantly correlated with single-strand breaks in DNA. The DraI polymorphism is also correlated with increased risk for lung cancer (33)(34)(35)(36)(37), for breast cancer among premenopausal smokers (38), and for renal carcinoma among Caucasian women (39). The RsaI c2 mutated allele in the 5Ј-flanking region was also associated with adenocarcinoma (40), esophageal cancer in a Chinese population (41), nasopharyngeal carcinoma (42), and oral cancer cases (43).…”
mentioning
confidence: 99%
“…A study of cardiovascular risk factors in 166 cigarette smokers revealed lower serum HDL cholesterol (0.76 vs. 0.81 mmole/l) and higher serum triglycerides (1.92 vs. 1.71 mmole/l) in comparison with values measured in 312 nonsmokers [236]. Higher triglyceride and total cholesterol levels have also been reported in other studies of smokers compared with non-smokers and ex-smokers [237][238][239][240][241][242][243][244][245]. A metaanalysis of data obtained in children and adolescents aged 8-19 years revealed associations between smoking (or non-smoking) status, and blood lipids and cholesterol fractions; the findings were analogous to those obtained in adults [228].…”
Section: Lipid and Cholesterol Metabolismmentioning
confidence: 76%